The Use of Drilling Method to Improve Students’ Vocabulary Mastery - Siahaan, Annatalia; Setiawan, Wawan; Surista, Ade (Sekolah Tinggi Bahasa Asing JIA, 2024)
This research focused on applying the drilling method to improve students’ vocabulary mastery at HKBP Kompas Indah. The drilling method is a method carried out by the teachers so that students can remember the new language items they have learned. With a quantitative approach and experimental research design, the researchers used pre-tests and post-tests. The participants involved were divided into control group and experimental group. The results showed that there was a significant increase in the pre-test and post-test scores in the experimental group. In contrast, the scores in control group had a decline from pre-test to post test. The mean score of post-test experimental group (89) was higher than pre- test experimental group (74). Therefore, the drilling method was effective to improve students’ vocabulary mastery at Sunday school HKBP Kompas Indah.